The Performance of The Sikka Regency Health Service To Be Called The Sustainable Development Goals (SDGs) in Reducing Maternal and Child Mortality Rates - Sia WILFRIDA; Hendrik TODA; Maria Magdalena LINO (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to determine the extent to which the performance of the Sikka District Health Office is achieving the Sustainable Development Goals of Reducing Maternal and Child Mortality Rates, and what are the supporting and inhibiting factors in providing maternal and child health services. The method used is qualitative, where the research is descriptive. The collection technique used is interviews with informants who have the potential to provide information related to the research, as well as observation and documentation methods. The results show an increase in the performance of the health office in several indicators, although some are not yet optimal. There are several main obstacles faced, such as the distribution of health workers, access to remote areas, and limited public understanding of the importance of maternal and child health services. The infrastructure for complaint services is still not optimal. Meanwhile, the form of internal and external accountability at the Sikka District Health Office has been running well, such as the services provided, especially in each Community Health Center covered by the Sikka District Health Office, are in accordance with the applicable Standard Operating Procedures (SOPs) and monthly monitoring and evaluation of performance achievements. Then, the preparation of activity reports is carried out monthly and annually.